KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEBSITE PADA INSTALASI ELEMEN BAKAR EKSPERIMENTAL PTBN SERPONG TANGERANG SELATAN - Sundari, Jenie (Jurnal Pilar Nusa Mandiri, 2014)
Knowledge Management is integrated approaching for any discipline which has a level for creating, for growing, for modifying and formulating it as specified, to arrange and share it, to use and to grow it for getting a good company’s future at the last. In IEBE Institute, implementation of knowledge management was running but not effective yet cause there are no some tools for supporting improving a good knowledge management system. Whereas the sharing still not good yet and in applying is still on manually. For supporting KMS as a writer I instruct for using web media online as a KMS tool’s system. Is web media online as great tools or no, it was made a few questions list for a worker in other to know the report. With work analyzing and activity method, will find that the web report can finish some problems which happened. And be applying it easily and fully in any places.